2021
DOI: 10.1038/s41366-021-00788-4
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss and risk reduction of obesity-related outcomes in 0.5 million people: evidence from a UK primary care database

Abstract: High body mass index (BMI) is known to be associated with various conditions, including type 2 diabetes (T2D), osteoarthritis, cardiovascular disease (CVD) and sleep apnoea; however, the impact of intentional weight loss on the risk of these and other outcomes is not well quantified. We examined the effect of weight loss on ten selected outcomes in a population from the UK Clinical Practice Research Datalink (CPRD) GOLD database. Included individuals were >18 years old at the index date (first BMI value bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
85
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 32 publications
2
85
0
2
Order By: Relevance
“…Obesity is a disease on pandemic proportions, affecting over 650 million individuals worldwide, where the prevalence is highest in the developed world and is associated with low socio-economic status [5]. Obesity is associated with excess adiposity and increases the risk of developing serious comorbidities including type 2 diabetes mellitus, cancer, musculoskeletal diseases, cardiovascular diseases, metabolic syndrome, mental health issues and premature death [2,3,6]. However, obesity is a modifiable disease where BMI reduction confers improvement of the comorbid conditions and can be curative [6].…”
Section: Obesity: Epidemiology Pathogenesis and Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity is a disease on pandemic proportions, affecting over 650 million individuals worldwide, where the prevalence is highest in the developed world and is associated with low socio-economic status [5]. Obesity is associated with excess adiposity and increases the risk of developing serious comorbidities including type 2 diabetes mellitus, cancer, musculoskeletal diseases, cardiovascular diseases, metabolic syndrome, mental health issues and premature death [2,3,6]. However, obesity is a modifiable disease where BMI reduction confers improvement of the comorbid conditions and can be curative [6].…”
Section: Obesity: Epidemiology Pathogenesis and Treatmentsmentioning
confidence: 99%
“…Obesity is associated with excess adiposity and increases the risk of developing serious comorbidities including type 2 diabetes mellitus, cancer, musculoskeletal diseases, cardiovascular diseases, metabolic syndrome, mental health issues and premature death [2,3,6]. However, obesity is a modifiable disease where BMI reduction confers improvement of the comorbid conditions and can be curative [6].…”
Section: Obesity: Epidemiology Pathogenesis and Treatmentsmentioning
confidence: 99%
“…Weight reduction, either through a surgical or non-surgical approach, has been shown to have positive effects on CV physiology. A study by Haase and colleagues [41] reported that a 13% reduction of body weight in patients with obesity significantly reduced CVD risks, including diabetes, hypertension and dyslipidemia. Moreover, studies also showed that patients with obesity who lost their weight had lower systolic blood pressure, HbA1c, low-density lipoprotein (LDL), triglycerides and CRP, and a higher high-density lipoprotein (HDL) [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Weight reduction, either through surgical or non-surgical approach, has been shown to have positive effects on CV physiology. A study by Haase and colleagues (33) reported that a 13% reduction of body weight in obese patients significantly reduced CVD risk, including diabetes, hypertension and dyslipidemia. Moreover, studies also showed that obese patients who lost their weight had lower systolic blood pressure, HbA1c, low-density lipoprotein (LDL), triglycerides and CRP, and a higher high-density lipoprotein (HDL) (33, 34).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Haase and colleagues (33) reported that a 13% reduction of body weight in obese patients significantly reduced CVD risk, including diabetes, hypertension and dyslipidemia. Moreover, studies also showed that obese patients who lost their weight had lower systolic blood pressure, HbA1c, low-density lipoprotein (LDL), triglycerides and CRP, and a higher high-density lipoprotein (HDL) (33, 34). Non-surgical approaches, such as lifestyle/diet modifications and pharmacological intervention, are the primary managements of obesity.…”
Section: Discussionmentioning
confidence: 99%